Youth Should Be Part of African Pharma Industry—A Perspective - Samuel Inshutiyimana (Health Science Reports)
ABSTRACT Background and Aim Africa imports over 70% of its medicines and 90% of its vaccines. This situation makes the citizens vulnerable to medicine shortages and increased risk of substandard and counterfeit drugs. This article provides insights into the significance of African youth in tackling key challenges affecting local pharma industry. Methods A literature review was conducted throughout September 2024 by retrieving articles from Google Scholar. Articles relevant to the aim of the study were snowballed, reviewed, analyzed, and considered during the preparation of this article. Results African youth possess fresh energy, minds, and innovative skills, which are indispensable for the development of local pharmaceutical sector. They are capable of utilizing artificial intelligence, which can advance critical processes in the African pharma industry including research and development (R&D) as well as quality assurance. Nevertheless, inadequate access to education, training, and mentorship opportunities hinder their involvement. Conclusion Established partnerships among local and international pharma industries, African universities, and other relevant stakeholders are essential to meaningful involvement of youth in the local pharma sector.